VITAMIN K - THE IGNORANT NUTRIENT - Chaudhary, Sushim (International Journal of Clinical and Biomedical Research, 2016)
Vitamins are widely classify as water soluble and fat soluble vitamins. Fat soluble Vitamin K is called as "Forgotten Vitamin" due to the important vitamin that are usually over looked by Scientist and Nutritionist. The name Vitamin K is discovered from German word Koagulation because vitamin K play important role in blood coagulation. Vitamin K is found in the dark green vegetables and vitamin. The main source of this vitamin are not found in leafy green vegetables and that is vitamin K1, which responsible for blood clotting and serves a different Function than K2. KEYWORDS Water soluble vitamins; Koagulation; Vitamin K; Green vegetables.